A Bibliometric Analysis of China–Latin America Economic and Political Relations. (29th October 2020) - Gil‐Barragan, Juan M.; Aguilera‐Castillo, Andres; Suárez Galeano, Llanet
Abstract : This article shares the results of a bibliometric analysis of the literature on the economic and political relations between China and Latin America. This review resulted in the identification of the leading research themes, intellectual structure, and main trends in this academic field. It also proposes a research agenda for future studies. An analysis of 102 documents that included articles, books, and book chapters was carried out through a bibliometric analysis and bibliographic coupling. The analysis shows that this topic has been developed through three stages. The first stage was composed of articles that investigated mainly bilateral economic relations. The second evaluates a possible negative "China effect" on Latin American countries, such as the reprimarization of the Latin American economy, the lost market share to China, and the increasing competitive pressures on the manufacturing sector. The third stage is an analysis of other dimensions, such as the implications of China–Latin America relations as part of the evolution of the world order, and Chinese investment as a political tool in Latin America. Finally, we found that, despite the research progress in these three stages, coverage of the topic is in a relatively incipient phase. Abstract : Este artículo presenta los resultados de un análisis bibliométrico sobre las relaciones económicas y políticas entre China y América Latina. A través de esta revisión de literatura, se identificaron los principales temas de investigación, la estructura intelectual y las principales tendencias en este campo académico. Adicionalmente, se propone una agenda de investigación para futuras investigaciones. El análisis bibliométrico se basó en la revisión de 102 documentos que incluye artículos, libros y capítulos de libros. Este análisis constató de una revisión bibliométrica y acoplamiento bibliográfico. El resultado muestra que este campo de investigación se ha desarrollado a través de tres etapas. La primera está integrada por artículos que investigan las relaciones económicas bilaterales. La segunda consiste en la evaluación de un posible "efecto negativo" de la relación económica entre China y los países latinoamericanos, como lo son la re‐primarización de la economía latinoamericana, la pérdida de participación de mercado en China y las crecientes presiones competitivas en el sector manufacturero. La tercera etapa está conformada por un análisis que incluye otras dimensiones, como las implicaciones de las relaciones entre China y América Latina como parte de la evolución del orden mundial y la inversión de China como herramienta política en América Latina. Finalmente, encontramos que, a pesar de los avances de estas tres etapas, este tema es un área de investigación relativamente incipiente. Abstract : 通过对中国与拉丁美洲的经济及政治关系进行文献计量分析，本文得出了结果。这一综述识别了该学术领域中的重要研究主题、知识结构和主要趋势。本文就未来研究提出一项研究议程。通过文献计量分析和文献耦合，开展了一项包括文章、书籍、书籍章节在内的102个文件分析。分析表明，该主题经过三个发展阶段。第一阶段由主要研究双边经济关系的文章组成。第二阶段评价了拉美国家可能受到的消极"中国影响"，例如拉美经济回到以初级商品作为出口收入的主要来源（reprimarization）、拉方损失的市场份额、以及对制造业产生的竞争压力加大。第三阶段对其他维度展开分析，例如中拉关系作为世界秩序演变的一部分、以及中国投资作为拉美政治工具所产生的意义。最后我们发现，尽管研究进程以这三个阶段展开，但对该主题的研究还处于相对初期阶段。